An application of the virtual reality 360° concept to the Great Zimbabwe monument - Njerekai, Cleopas (Taylor and Francis Ltd., 2021)
This paper is an application of the virtual reality 360° concept to the Great Zimbabwe monument to produce virtual tour videos of this world-scale heritage site. The paper was prompted by the need to make this tourist magnet accessible to the physically challenged, and those constrained by finance, distance and time. It was also prompted by the need to better inform and educate guests about the monument and possibly increase visitation as several studies have showed that three dimensional virtual tours may increase actual intention to visit. To produce the virtual videos, spherical images of the monument were first shot with a 360° camera and then stitched in Kolor Autopano software to get high-resolution images. The virtual tour videos are expected to be uploaded on a server for access by the entire world on computers, tablets and smartphones for a fee. The videos allow patrons to navigate the monument’s key archeological sites, such as the Great Enclosure and the Valley Ruins, as well as listen to highly educational and informative commentaries. As this project is the first of its kind in Zimbabwe, this paper suggests that follow-up research on the videos should be undertaken to establish their impact.